Concurrent Resistance Training and Flying 200-Meter Time Trial Program for a Masters Track Cyclist. Issue 3 (June 2016) - Del Vecchio, Luke; Villegas, Jerome; Borges, Nattai; Reaburn, Peter
Abstract : ABSTRACT: PARTICIPATION NUMBERS IN MASTERS TRACK CYCLING DEMONSTRATE THAT TRACK CYCLING IS BECOMING AN INCREASINGLY POPULAR SPORT FOR MASTERS ATHLETES. DESPITE THIS, RESEARCH FOCUSED ON PERFORMANCE ENHANCEMENT FOR MASTERS TRACK CYCLISTS IS LACKING. AGE-RELATED CHANGES IN MORPHOLOGICAL AND NEUROMUSCULAR FACTORS AFFECT SPRINT PERFORMANCE AND PRESENT STRENGTH AND CONDITIONING COACHES WITH SIGNIFICANT CHALLENGES. THIS ARTICLE THEREFORE AIMS TO JUSTIFY THE INCLUSION OF A CONCURRENT RESISTANCE TRAINING AND FLYING 200-M TIME TRAIL PROGRAM AS AN INTERVENTION TO INCREASE THE FLYING 200-M PERFORMANCE OF A MASTERS TRACK CYCLIST (SEE, VIDEO, SUPPLEMENTAL DIGITAL CONTENT 1, http://links.lww.com/scj/a182 ). Abstract : Supplemental Digital Content is Available in the Text.